Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Collins, HM; Pinacho, R; Tam, SKE; Sharp, T; Bannerman, DM; Peirson, SN (Springer Nature, 2023)
Rationale: Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation.